Study on the Determination of Polycyclic Aromatic Hydrocarbons (PAHs) in Fingernail and Hair Samples by Gas Chromatography Mass Spectrometry (GC/MS) - Trang, Vu Thi; Hieu, Nguyen Duc; Duyen, Nguyen Thi; Thao, Nguyen Xuan; Ngoc, Pham Hong; Thai, Pham Hong; Thuy, Phan Thi Thanh; Huong, Nguyen Thi Anh; Anh, Hoang Quoc (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 1, 2024)
Information about human exposure to polycyclic aromatic hydrocarbons (PAHs) in Vietnam is still very limited. In this study, an accurate method for the determination of 16 PAHs in human hair and fingernail samples was developed. The nail and hair samples were digested in sodium hydroxide solution. PAHs in the digested solutions were extracted using organic solvents such as hexane and dichloromethane. The extracts were cleaned up by using solid phase extraction (SPE) cartridges containing silica gel with dichloromethane/hexane mixture as elution solvent. PAHs were quantified by a gas chromatography/mass spectrometry (GC/MS) system operated in electron impact ionization and selected ion monitoring (EI/SIM) mode. The liquid-liquid extraction and SPE clean-up steps were investigated to obtain acceptable recovery of PAHs before application to nail and hair samples. Recovery of PAHs in spiked nail and hair samples ranged from 66% to 112%, indicating acceptable method accuracy. Concentrations of 16 PAHs in the nail and hair samples were 160 and 733 ng/g, respectively. Major PAHs found in the nail and hair samples were naphthalene, phenanthrene, fluoranthene, and pyrene. Additional studies on human biomonitoring of PAHs and their related compounds should be conducted in Vietnam.